Alfabetização e letramento : um estudo com professoras alfabetizadoras acerca da apropriação de novos enfoques teóricos - Dias, Rosângela Hanel (2007)
This work interferes in the field of studies on alphabetization and literacy, with views to understand in that measured the access to a new concept, in this case specific of the literacy, it contributes to the enlargement of the your know that orientate the pedagogic practice of teachers alphabetizers, deepening them, complexing them and exposing your limitations. It is had by hypothesis that the conceptual maps drawn in the academic ambit but they compete with the knowledge educational coming of the practice than for a deeper reflection about the reaches, fragilities and potentialies of that practice. To investigate it, a conceptual revision is accomplished on alphabetization and literacy with base in the which they are exposed some implications pedagogic that appear starting from the inclusion of those terms in the educational contexts. It is accomplished, still, a ruled empiric study in the of a municipality inside Rio Grande do Sul. The dates were analyzed with base in two categories: alphabetization conception and literacy and scientific knowledge and practical knowledge. To the dynamics established interlocution in the group made possible to locate some fragilities in the relationship between the academic world and the world of the school and to put in question the possibilities that propositions and disjointed of the teaching practices lived at the schools they have to unchain significant innovations in the reflection on the pedagogic work and more precisely in the touching educational actions to the process of acquisition of the written language